Job satisfaction and competence's impact on employees' performance at the office Subdistrict Cileunyi Regency Bandung - Djoko Soelistya; Euis Heryati; Muhammad Ade Kurnia Harahap; Angga Kurniawan (Program Pascasarjana STIE Amkop Makassar, 2023)
This study aims to determine the effect of competency and job satisfaction partially, and which variable between the two independent variables has the most dominant effect on the dependent variable on Office Subdistrict Cileunyi Regency Bandung. Study This method quantitative. Data Which used data primary And data secondary. Population study amount 21 person. Taking sample his research was population research, the technique used was total sampling. Data collection technique done by distributing questionnaires. Data analysis technique using multiple linear regression with use application computer ( Statistical Packages for Social Scienceties ) SPSS-25. Results study concluded that the competency variable partially had no effect on employee performance at Cileunyi District Office, Bandung Regency, and partial job satisfaction has a significant effect to performance employee on Office Subdistrict Cileunyi Regency Bandung, results from variable Job satisfaction has the most dominant effect compared to competence on employee performance at the office Subdistrict Cileunyi Regency Bandung. Keywords: Competence, Satisfaction Work, Performance Employee